PENGARUH PROMOSI, KEMUDAHAN, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI SISTEM E-COMMERSE SHOPEE PADA PENGGUNA APLIKASI SHOPEE DI KECAMATAN MAMASA KABUPATEN MAMASA - ASTIANA; MUSTARI; TUTI SUPATMININGSIH; MUHAMMAD IHSAN SAID; MUHAMMAD HASAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to explain how the effect of promotion, convenience, and trust for Shopee application users in Mamasa District, Mamasa Regency when making purchases with an e-commerce system. In this study used quantitative research. Observation, questionnaire, and documentation are survey methods used to collect data. The population of this study consisted of 100 respondents who had used the shopee application to do online shopping in Mamasa sub-district. Multiple linear analysis was used to test the relevant data. According to the study’s findings, the third variable (X) simultaneously has a big impact on the Mamasa community’s purchasing choices (Y). However, the Promotion variable (X1) and the Ease variable (X2) partially have no significant effect on the Y variable. While the Trust variable (X3) has a significant effect on the variable (Y).